Comparative transcriptome profiling reveals the importance of GmSWEET15 in soybean susceptibility to Sclerotinia sclerotiorum - Xiao, Kunqin; Qiao, Kaibin; Cui, Wenjing; Xu, Xun; Pan, Hongyu; Wang, Fengting; Wang, Shoudong; Yang, Feng; Xuan, Yuanhu; Li, Anmo; Han, Xiao; Song, Zhuojian; et al. (Frontiers in Microbiology, 2023)
Soybean sclerotinia stem rot (SSR) is a disease caused by Sclerotinia sclerotiorum, which causes incalculable losses to soybean yield every year. Suffering from the lack of effective resistance resources and the elusive resistance mechanism, we are urged to develop resistance genes and explore their molecular mechanisms. Here, we found that loss of GmSWEET15 enhanced the resistance to S. sclerotiorum, and then explored the molecular mechanism of gmsweet15 mutant enhancing the resistance to S. sclerotiorum by comparing transcriptome. At the early stage of inoculation, compared with the wild type, which activated part of the defense response pathway, gmsweet15 mutant showed more extensive and intense transcription reprogramming, which not only enriched more biological processes, such as secretory pathway and tetrapyrrole metabolic, but also had more drastic changes in defense response, protein ubiquitination, MAPK signaling pathway-plant, plant-pathogen interaction, phenylpropanoid biosynthesis and photosynthesis. These more intense and abundant transcription reprogramming of gmsweet15 mutant may be the reason why it effectively delays the colonization of S. sclerotiorum. In addition, we also identified common and specific DEGs between WT and gmsweet15 mutant after inoculation with S. sclerotiorum by venn diagram, and gene sets and genes related to gmsweet15_24 h by GSEA. Moreover, we constructed PPI network and gene co-expression network and identified several groups of regulatory networks of gmsweet15 mutant response to S. sclerotiorum, which are helpful for the discovery of candidate functional genes. Together, our results reveal that the molecular mechanism of delaying the colonization of S. sclerotiorum after the loss of GmSWEET15 in soybean, and provided abundant resources for elevating SSR resistance.